Teaching Intercultural Communicative Competence (ICC) at the AFL Novice Level: Teachers’ Practices and Constraints - Fahmy, Nancy (AUC Knowledge Fountain, 2026)
Intercultural Communicative Competence (ICC) is widely recognized as a core objective in language education; however, its implementation in novice-level Arabic as a Foreign Language (AFL) classroom remains insufficiently examined. This study explores what strategies do AFL teachers use to integrate ICC principles at the beginner level (A1–A2), the constraints that shape classroom practice, teachers’ assessment approaches, and perceived professional development needs. Using an explanatory sequential mixed-methods design, quantitative data were collected through a bilingual (Arabic–English) online survey completed by 54 AFL teachers working across instructional contexts in Egypt, Jordan, the United Kingdom, and the Netherlands. Qualitative data were subsequently gathered through six semi-structured interviews to provide contextualized insights into teachers’ pedagogical decision-making and classroom practices. Findings reveal that although many teachers are unfamiliar with ICC as a formal theoretical framework, they frequently implement practices that align with key ICC principles. These practices are primarily embedded within communicative classroom routines, including role-plays, guided cultural comparison, mediated use of authentic materials, and sociolinguistic explanation related to Arabic diglossia. ICC integration at the novice level is therefore characterized as implicit, interaction-focused, and developmentally adapted rather than systematic or explicitly articulated. At the same time, teachers report persistent challenges, including limited instructional time, curriculum constraints, cognitive load for beginner learners, and the absence of level appropriate ICC assessment tools. The study highlights a gap between theoretical ICC models and classroom realities in novice AFL instruction and underscores the need for targeted professional development,  curricular support, and assessment frameworks that make intercultural objectives more  visible, intentional, and sustainable.